2019
DOI: 10.7717/peerj.7027
|View full text |Cite
|
Sign up to set email alerts
|

Biochar prepared at different pyrolysis temperatures affects urea-nitrogen immobilization and N2O emissions in paddy fields

Abstract: Background Food safety has become a major issue, with serious environmental pollution resulting from losses of nitrogen (N) fertilizers. N is a key element for plant growth and is often one of the most important yield-limiting nutrients in paddy soil. Urea-N immobilization is an important process for restoring the levels of soil nutrient depleted by rice production and sustaining productivity. The benefits of biochar application include improved soil fertility, altered N dynamics, and reduced nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Therefore, immobilization and volatilization could also explain the negative effect of biochar. Similarly, Gao et al (2019) and Güereña et al (2015) found that biochar combined with mineral fertilizer decreased grain yield, and the yield reduction under biochar produced at a higher temperature (700 °C) was lower than that produced at 400 °C (Gao et al 2019). The results of the present study imply that biochar should be applied at a higher rate in high P-fixing soils to ensure its beneficial effect on yield.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, immobilization and volatilization could also explain the negative effect of biochar. Similarly, Gao et al (2019) and Güereña et al (2015) found that biochar combined with mineral fertilizer decreased grain yield, and the yield reduction under biochar produced at a higher temperature (700 °C) was lower than that produced at 400 °C (Gao et al 2019). The results of the present study imply that biochar should be applied at a higher rate in high P-fixing soils to ensure its beneficial effect on yield.…”
Section: Discussionsupporting
confidence: 57%
“…Nitrogen is one of the three major chemical fertilizers applied in rice production, and its application level, timing, and management mode significantly affect rice yield and NUE [9,[29][30][31][32]. In the current study, the responses of the three cultivars to different N rates were significantly different.…”
Section: Discussionmentioning
confidence: 60%
“…The ratios of alkyl C/O-alkyl C, aromatic C/aliphatic C, and hydrophobic C/hydrophilic C increased in response to BC treatment compared to SR and CK. Our findings suggested that biochar amendment could enhance the long-term storage of SOC both via macroaggregate protection and via the stability of SOC (Gao et al, 2019b).…”
Section: Discussionmentioning
confidence: 74%
“…Biochar is considered an ideal material for carbon sequestration due to its stable properties. Biochar as a soil amendment can enhance crop yield (Mahmoud et al, 2019;Ali et al, 2020), improve soil total porosity and the water-holding capacity (Gao et al, 2019b), and decrease the bio-availabilities of heavy metals and organic pollutions (He et al, 2018;Xia et al, 2019). Biochar contains high amounts of carbon and has considerable potential for increasing the SOC content.…”
Section: Introductionmentioning
confidence: 99%